VISUAL COMMUNICATION ANALYSIS IN SPORTS PHOTOGRAPHY ON INSTAGRAM @EXPLOREPERSIB: A QUALITATIVE DESCRIPTIVE STUDY - Sabillillah Josha; Tanto Trisno Mulyono (TOPLAMA, 2026)
This study analyzes visual communication in sports photography on Instagram @explorepersib and examines the creative workflow from image capture to publication. The research is motivated by the dominance of sports photography as primary content and strong audience responses, yet constrained by the absence of formal standards, creative misalignment between photographer and media team, and situational field challenges. Conducted on the Instagram account @explorepersib, this study employed a qualitative descriptive method with in-depth interviews, documentation of posts, and non-participant observation. Findings reveal that visual communication is shaped through news value, match atmosphere, and the EDFAT technique to produce varied visual narratives, while the creative process prioritizes photo selection based on news value, aesthetics, and engagement potential. The study concludes that consistent EDFAT use, clear selection standards, and proper workflow documentation are essential to maintain content quality and visual storytelling strength.